Economics of dairy farming and marketing: Micro-level perspectives from three major milk producing states of India - KUMAR, ANJANI; PARAPPURATHU, SHINOJ (The Indian Journal of Animal Sciences, 2014)
The study attempted farm level analysis of production and marketing behaviour of dairy farmers, in three major milk producing states, namely Punjab, Bihar and Uttar Pradesh of India. These states represent geographic and institutional diversity of milk production and marketing in India. The study also identified the major constraints faced by the dairy farmers and suggested policy prescriptions for creating future opportunities for the resource poor farmers and entrepreneurs engaged in this sector.